The effect of filler loading and silane coupling agent on properties of rice husk powder filled natural rubber compounds / Razif Nordin, Said C. S. and Ismail H. - Nordin, Razif; C. S., Said; H., Ismail (Universiti Teknologi MARA, Perlis, 2010)
The effect of silane coupling agent, bis(triethoxysilyl propyl) tetrasulphide, Si69 on cure characteristics and mechanical properties of rice husk powder, RHP filled natural rubber, NR compounds were studied. Scorch time t2 and cure time t90 of the compounds decrease with increasing filler loading and with presence of a silane coupling agent, Si69. However, minimum torque increases with increasing filler loading but at a similar filler loading shows lower value with the presence of Si69. The mechanical properties of compounds viz tensile strength, tensile modulus and hardness were also increased while resilience decreases with additional of Si69